Konsumsi Buah Teratai (Nymphea sp) Sebagai Determinan Terjadinya Fasciolopsis Buski pada Anak - Muhamad Muslim; Rifqoh Rifqoh; Irwandi R (Medical Laboratory Technology Journal, 2016)
Fasciolopsis buski is a health problem that is difficult to eradicate. Fasciolopsis buski infection is caused by ingested metacercariae that live on aquatic plants. One factor that supports the transmission mechanism of Fasciolopsis buski, of which there are still some people, especially children who have a habit of eating Nymphea sp. The study aims to determine the relationship with lotus fruit consumption habits with Fasciolopsis buski infection. The type of research is analytic survey with cross sectional approach, the study samples are 69 students of Sungai Papuyu primary school consists of 38 men and 31 women, the technique of sampling is random sampling (simple random), research instruments are using questionnaires and microscopic examination of worm eggs, data analysis is using the Chi-square. Students are accustomed to eating Nymphea sp of crude (not good) are 31 people (44.93%), and are not familiar (well) are to 38 people (55.7%). A total of 7 people (10:14%) are infected Fasciolopsis buski and 62 (89.86%) are not. Students who are infected Fasciolopsis buski entirely used to eat fruit lotus. Based on the statistical test Chi-Square, there is a relationship between the habit of eating Nymphea sp with lotus Fasciolopsis buski infection with the value of Fisher's Exact Test 0,002 less than the value ? of 0.05. The habit of eating Nymphea sp are associated with infections to the students.